Analisis Nilai Profil Pelajar Pancasila dalam Cerita Rakyat Anggasuto pada Pendidikan Sekolah Dasar - Andi Irawan; Suriyani Suriyani; Vita Nur Oktavia; Mas’odi Mas’odi (Journal on Education, 2025)
This research aims to analyse the values of Pancasila learner profile in Anggasuto folklore from Pinggir Papas village. This research uses qualitative method with narrative analysis research model to analyse the structure, meaning, and values of Pancasila learner profile in Anggasuto folklore. The data sources in this research are primary data, namely folklore conveyed through the speech of sources. Then secondary data, in the form of written documents in the form of manuscripts, articles, and notes related to Anggasuto folklore. The data collection techniques used were interviews, observations, and documentation studies. The data analysis technique in this research includes three stages, namely the data reduction stage, the data presentation stage, and the conclusion drawing and verification stage. The results of this study show that in Anggasuto folklore there are values that are relevant to the Pancasila Student Profile, namely in the dimensions of faith and piety in God Almighty, global diversity, mutual cooperation, independence, critical reasoning, and creativity.